Penerapan Model Pembelajaran Berbasis Masalah Berbantuan Liveworksheet untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika - Paramartha, I Putu Wahyu; Prayitno, Sudi; Gunawan, Gunawan; Prabandari, Ida Ayu Dewi (Mandalika Mathematics and Educations Journal, 2024)
This study proposes to improve students' learning activities and learning outcomes math in class X.12 SMAN 2 Mataram in the academic year 2023/2024. The type of this research is class action research conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data on student learning activities were obtained through observation, and data on student learning outcomes were obtained through evaluation tests at the end of each cycle. The learning activities of students in cycle I were in the active category, then increased in cycle II with a very active category. As for the learning outcomes of students, there was also an increase in the percentage of students' classical completeness in cycles I and II, which were 75% and 86%, respectively. Therefore, it can be concluded that implementing the problem-based learning model aided by Liveworksheet on subject statistics can increase the activity and learning outcomes math of students in the class X.12 SMAN 2 Mataram in the academic year 2023/2024.